Bioethics, genetics and sport - Camporesi, Silvia (Bioethicist); McNamee, M. J. (Mike J.) (London New York Routledge, Taylor & Francis Group, 2018)
Advances in genetics and related biotechnologies are having a profound effect on sport, raising important ethical questions about the limits and possibilities of the human body. Drawing on real case studies and grounded in rigorous scientific evidence, this book offers an ethical critique of current practices and explores the intersection of genetics, ethics and sport. Written by two of the world's leading authorities on the ethics of biotechnology in sport, the book addresses the philosophical implications of the latest scientific developments and technological data. Distinguishing fact from popular myth and science fiction, it covers key topics such as genetic basis of sport performance and the role of genetic testing in talent identification and development. Its ten chapters discuss current debates surrounding issues such as the shifting relationship between genetics, sports science, gene enhancement, gene transfer technology, doping and disability sport.
1. The nature of genetics and its place in medicine and sport -- 2. What role for genetic testing in sport? -- 3. Genetic testing for talent identification and development -- 4. Biobanking in sport: governance and ethics -- 5. Gene transfer, gene enhancement and gene doping: distinguishing science from science fiction -- 6. Enhancement, doping and the spirit of sport -- 7. A case study in 'gene enhancement': gene transfer to raise the tolerance to pain - a legitimate mode of enhancement, or illegitimate doping? -- 8. On the eligibility of female athletes with hyperandrogenism to compete: athleticism, medicalisation and testosterone -- 9. Congenital and acquired disabilities: what counts as unfair advantage in the Paralympics? -- 10. the re-inscription of the concept of biological race through sport in society
Includes bibliographical references and index
Keywords: Athletic ability; Human genetics; Sports -- Physiological aspects; Sports medicine -- Moral and ethical aspects